English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1.(x+4)(x-3)=0

2.x^2+6x+9=0

3. y=6-x
y=-4x+3

4. Y=5-3x
3x+2y=8

2007-02-01 14:55:32 · 1 answers · asked by User84 4 in Science & Mathematics Mathematics

1 answers

1.(x+4)(x-3)=0

x+4=0: X-3=0
x=-4; x=3

2.x^2+6x+9=0
(x+3)(x+3)=0
x+3=0
x=-3

3. y=6-x
y=-4x+3
sub 6-x for y in the second equation
6-x=-4x+3
-6+4x = -6+4x
-x+4x=3-6
3x=-3
x=-1
y=6-x
y=6--1
y=6+1
y=7
x=-1; y=7

4. Y=5-3x
3x+2y=8

3x+2(5-3x)=8
3x+10-6x=8
-3x+10=8
-3x=8-10
-3x=-2
x=2/3

2007-02-01 15:06:35 · answer #1 · answered by Bill F 6 · 0 0

fedest.com, questions and answers